326—Conservation in the age of the robot. Issue 2 (4th May 2017) - McCapra, Alastair
Abstract: Artificial intelligence (AI) systems are already playing an increasing role in many areas of professional activity, including the law, accountancy, building design and communications. This paper considers the types of activity which are likely to be largely replaced by AI in the near future and what the impact of AI could be on the conservation profession. It concludes that because of the hybrid nature of their work, conservators are probably less likely to be affected than many other professions, although the mix of tasks they undertake could be changed considerably in the near future. In particular, this paper argues that there may be less management-related activity in the future work of conservators, and more interventive, object-based work.